Fuzzy Models for the Common Evaluation and Analysis of Entity’s Financial Position - Kirov, Georgi; Velkov, Yulian (Research Papers, 2011)
The research is dedicated to problems related to the development of a complex assessment and analysis of the entity’s financial position. The disadvantages of the traditional methods in respect to the dynamic of economic environment and uncertainty in expert opinions are analyzed. The critical need for new innovative approaches taking into account the user preferences and complexity of the management decisions is shown. A fuzzy model for an assessment and analysis of the entity’s financial position is developed. It assesses the criteria working capital and capital structure as key features of the financial position using the principles of the fuzzy logic. Important limitations of the traditional methods of the analysis are overcome by the fuzzy model. It improves the complexity of the financial condition and creates a comprehensive basis for a factor analysis. A control example is developed through modeling and simulation tools. The research team has gone through all stages of the life cycle of a complex system, starting from the early stages of the study and system analysis and ending with implementation and testing.